Asymmetric rectilinear ion trap with unidirectional ion ejection capability. (12th August 2020) - Huo, Xinming; Chen, Dong; Tian, Yuan; Li, Man; Yu, Quan; Guo, Cheng'an; Wang, Xiaohao
Abstract: In this paper, the shapes of the electrodes are modified based on a rectilinear ion trap to achieve unidirectional ejection of ions. The designed asymmetric rectilinear ion trap (ARIT) analyzer adds convex and concave circular structures with a height of 0.5 mm on the two X‐electrodes, so that the electric field center of the ion trap is inclined to the concave side. The electric field lines of the convex side are compressed to the concave side. Both simulations and experimental results show that ions are more likely to emit from the slit on the concave side plate when performing ion resonance ejection. The mass spectrum signal intensity can reach more than twice that of the original rectilinear trap when using only one detector. Calculations of the electric field components in the trap show that the even‐order higher field proportion in the ion trap has not been significantly affected. Combined with the experimental test results, the study further confirmed that the developed ARIT has no significant loss in mass resolution, tandem mass spectrometry capability, and quantitative analysis capability. The proposed asymmetric structure modification scheme can achieve single‐side ejection without significantly affecting other performances of the analyzer, which provides a new idea for the structural optimization of the subsequent ion trap analyzers.